Randomized clinical trial. Effect of two types of fasting in patients undergoing percutaneous intervention procedures under local anesthesia in a hemodynamic service in Medellín, 2019 - Cortés Hernández, Heidi Andrea; Marín Escobar, Seneth; Ortiz Pérez, Lina Constanza (Medicina UPB, 2023)
Objective: to determine the effect of two types of fasting on parameters of satisfaction, nausea, vomiting, blood pressure and glucose measurement in patients undergoing percutaneous intervention procedures under local anesthesia in a hemodynamic service in Medellín, 2019. Methodology: Two-arm open-label randomized clinical trial in patients undergoing percutaneous interventional procedures under local anesthesia for three months, each arm with 153 participants, who were assigned a six-hour fast and the exposure group a two-hour fast for easily digestible foods. There was no blinding, sample calculation was performed, and univariate and bivariate analysis and logistic regression model were performed with the satisfaction variable.Results: in the six-hour fasting group, 2.6% presented nausea and in the exposure group, 1.3%; one case of vomiting was observed. Blood pressure and blood glucose showed statistical differences without clinical relevance. Statistical significance was found for dizziness, headache, hunger, thirst, and type of fasting with respect to patient satisfaction. Fasting patients had a satisfaction score between 60 and 100 and those on a light diet between 82.5 and 100 points.Conclusions: Fasting for two hours on a light diet improves patient satisfaction, decreases the sensation of hunger, thirst, headache and dizziness, compared to a six-hour fast. This study found no differences in the hemodynamic variables, nor in the frequency of nausea and vomiting.
Keywords: fasting; local anesthesia; angiography; hemodynamics